2013
DOI: 10.5897/ajmr2013.5631
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics usage in food-producing animals in South Africa and impact on human: Antibiotic resistance

Abstract: The widespread and intensive use of antibiotic agents in modern food production systems is believed to be contributing significantly to antibiotic resistance among bacteria. Antibiotic usage in foodproducing animals tend to be increasing and data show that even those that have been banned in other countries such as growth promoters are still being used in South Africa. Moreover, very few relatively recent surveys and reports on antibiotic resistance isolates from food animals in South Africa have been carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Through the perception of the veterinary students in Africa, tetracycline, penicillins, sulphonamides, macrolides, and aminoglycosides are the five most abused of all the antimicrobials used in Africa. This finding is in agreement with earlier studies in Ghana (44), South Africa (45), and Nigeria (46), and it should be a source of concern to stakeholders and the authorities. Regulatory authorities should intensify efforts to combat the continued misuse of these identified drugs and it becomes necessary to assess the situation in humans across Africa to see if the patterns are similar.…”
Section: Degree Of Abuse Of Antimicrobialssupporting
confidence: 93%
“…Through the perception of the veterinary students in Africa, tetracycline, penicillins, sulphonamides, macrolides, and aminoglycosides are the five most abused of all the antimicrobials used in Africa. This finding is in agreement with earlier studies in Ghana (44), South Africa (45), and Nigeria (46), and it should be a source of concern to stakeholders and the authorities. Regulatory authorities should intensify efforts to combat the continued misuse of these identified drugs and it becomes necessary to assess the situation in humans across Africa to see if the patterns are similar.…”
Section: Degree Of Abuse Of Antimicrobialssupporting
confidence: 93%
“…The spread of multidrug resistant bacteria can cause infections that are resistant to antibiotic treatment [58] and the transmission of residual antimicrobials through the food chain can trigger serious health problems, like gastrointestinal and neurological ailments, tissue damage, and hypersensitivity in animals and humans [59]. Therefore, the use of antimicrobials in food animal production should be minimized considering possible alternative options, like prebiotics, probiotics, and herbal extracts, for both prophylactic and therapeutic use in poultry production [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…It was associated with the possession of resistance genes that resulted from the therapeutic and prophylactic usage of advocin and chloramphenicol in animals. Furthermore, it was reported that resistance to tetracycline, ampicillin, amoxicillin, penicillin, and erythromycin is associated with the possession of resistance genes to these antibiotics, as a result of the widespread use of chlortetracycline, amoxicillin, penicillin, and erythromycin in intensive animal rearing either for disease control or as feed supplements or growth promoters [33, 40]. Coselection of resistance genes located on the same mobile genetic elements does occur as a result of the usage of different antibiotics in animal rearing [11–16].…”
Section: Discussionmentioning
confidence: 99%